Uji Efek Teratogen Ekstrak Etanol Daun Sirsak (Annona muricata L) Terhadap Fetus Mencit Putih - Ifora, Ifora; Suhatri, Suhatri; Yolandha, Suzie (Jurnal Farmasi Higea, 2016)
Research on test teratogenic effects of ethanol  extract of leaves of the soursop (Annona muricata L.) have been conducted on white mice fetus. Animal experiments are grouped into  4 group consisting of Group I as a negative control only granted suspension of Na CMC 0.5%, Group II, Group III and Group IV granted soursop leaf ethanol extract at a dose of 250 mg / kg, 500 mg / kg, and 1000 mg / kg once daily from day 6 to day 15 of pregnancy. The 18th day of pregnancy mice were dissected. Results of the study at a dose of 250 mg / kg, a dose of 500 mg / kg, a dose of 1000 mg / kg give teratogen effects. A dose of 250 mg / kg, a dose of 500 mg / kg give teratogen effect with the discovery of skeletal abnormalities. A dose of 1000 mg / kg give teratogen effect with the discovery of late growth. Results showed that the ethanol extract of the leaves of the soursop affect weight loss parent mice were significantly (p <0.05) when compared to the negative control. The quantity of fetuses decreased significantly (p <0.05) when compared to the negative control. Fetal body weight showed a significant effect (p <0.05) when compared to the negative control.